Pandangan Syed Muhammad Naquib Al-Attas Tentang Pendidikan Dan Relevansinya Dengan Teori Pendidikan Kontemporer - Farchan Nurhakim (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
Abstract: This article discusses the views of Syed Muhammad Naquib Al-Attas on education. The cause of the decline of Muslims in recent decades is the result of confusion in knowledge and the weakness of the people's mastery of science. This resulted in the weakening of Muslims in the political, economic, social, and cultural fields. Therefore, the researcher wants to describe the role, objectives, curriculum, educators, students, and contemporary educational methods according to Syed Muhammad Naquib Al-Attas. This study uses descriptive qualitative with the data that has been collected and then analyzed using the method of content analysis. The data collection technique uses documentation in the form of literature or archives, researchers will go into the field themselves, both in the grand tour question, focused and selection stage, collecting data, analyzing, and making conclusions. Based on the results of the discussion, among others: 1) Syed Muhammad Naquib Al-Attas defines education as a key concept that is the core of education and the educational process. He also pressed him about the education of etiquette. 2) Syed Muhammad Naquib Al-Attas curriculum, namely: fardu ain and fardu kifayah, namely Islamic education and science education. 3) Linking the concept of Syed Muhammad Naquib Al-Attas and the Law that discusses students, the authors can conclude that students are someone who tries to explore knowledge by achieving their goals through educators and without losing their manners as students. . 4) According to Syed Muhammad Naquib Al-Attas, an educator is a person in charge of transferring knowledge, or educating the soul and behavior of students in good manners so that they can be used as examples for students. 5) Syed Muhammad Naquib Al-Attas uses the monotheistic method, the metaphorical method. Of the five educational concepts relevant to contemporary theory. Keywords: Syed Muhammad Naquib Al-Attas View, Education, Contemporary Education